Evaluación de la actividad coagulante -floculante de la harina de Theobroma cacao para el tratamiento de las aguas del Río Nanay - Vásquez Flores, Gabino Segundo (2025)
The main objective of this research was to evaluate the coagulating activity of flour derived from the husk of Theobroma cacao L. in terms of its ability to eliminate turbidity and color. To achieve this objective, the chemical characteristics of the husk were systematically characterized, and the flour was produced through a grinding process. Subsequent jar tests were performed by varying the coagulant doses (0, 20, 40, 60, and 80 mg/L) along with varying slow stirring speeds (20, 30, and 40 rpm). The analyzed husk showed a moisture content of 82.67%, 11.47% carbohydrates, 1.20% protein, 0.03% fat, and 0.16% ash. Elimination was recorded with coagulant doses ranging from 60 to 80 mg/L at an agitation speed of 40 rpm, resulting in an elimination efficiency of between 93.27% and 98.9%. It can be concluded that cocoa flour exhibits significant coagulant properties, representing a viable natural alternative for water treatment